2017
DOI: 10.1016/j.jocn.2016.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Extreme lateral interbody fusion relieves symptoms of spinal stenosis and low-grade spondylolisthesis by indirect decompression in complex patients

Abstract: Spinal stenosis and low-grade spondylolisthesis produce symptoms of neural compression that can be treated with extreme lateral lumbar interbody fusion (XLIF) via indirect decompression. This study aimed to investigate whether the restoration of disc dimensions would relieve symptoms of radiculopathy, claudication and back pain. In this retrospective study, patients undergoing XLIF surgery for relief of radicular symptoms or degenerative disc disease were included. Radiologically proven changes were used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
43
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 29 publications
1
43
1
Order By: Relevance
“…The advantages of this technique include: (1) the indirect decompression of the neural elements, leaving the anterior and posterior longitudinal ligaments intact, (2) the restoration of the sagittal and coronal alignment of the spine, (3) a lower subsidence rate because of the implant of larger cages and (4) no damage caused to the paravertebral muscles compared to the conventional posterior arthrodesis and direct decompression techniques [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages of this technique include: (1) the indirect decompression of the neural elements, leaving the anterior and posterior longitudinal ligaments intact, (2) the restoration of the sagittal and coronal alignment of the spine, (3) a lower subsidence rate because of the implant of larger cages and (4) no damage caused to the paravertebral muscles compared to the conventional posterior arthrodesis and direct decompression techniques [2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional posterior techniques, this approach is also advantageous in revision surgery cases as it allows to reach the vertebral bodies avoiding the scar tissue from previous interventions [3,4,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…This procedure has been successfully used for obtaining effective reduction and favorable alignment through a minimally disruptive approach and indirect decompression of the spinal canal and intervertebral foramen. 2,21,25 A minimally invasive LLIF approach has been reported to reduce postoperative pain, tissue trauma, and operative and recovery times, thereby resulting in shorter hospital stays and brisker overall symptom improvement compared with traditional approaches. 22,25 Neurological complications associated with lateral approaches are frequently discussed in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…2,21,25 A minimally invasive LLIF approach has been reported to reduce postoperative pain, tissue trauma, and operative and recovery times, thereby resulting in shorter hospital stays and brisker overall symptom improvement compared with traditional approaches. 22,25 Neurological complications associated with lateral approaches are frequently discussed in the literature. 5,18 Previous anatomical and radiographic evaluations have identified that the lumbar plexus migrates dorsally to ventrally from L2-3 as the lumbosacral plexus descends caudally to the L4-5 and L5-S1 levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation